RESEARCHING STUDENTS’ CRITICAL THINKING IN ARGUMENTATIVE TEXTS (A Systemic Functional Linguistic Perspective) - Udi Samanhudi (University of Muhammadiyah Purwokerto, 2011)
This study aims to investigate students’ critical thinking as reflected in their argumentative writing in one state university in Serang, Banten. This study used a case study research design which employed two data collection techniques, i.e. the documentation of students’ essays and interview. The data were, then, analyzed based on the theory of Critical Thinking (CT) and Systemic Functional Linguistics (SFL) which were validated by triangulation. The study revealed two findings related to the research questions. First, results of the text analysis showed that despite their ability to show their critical thinking in their writing, students’ texts still showed that the verbalization of the students’ critical thinking was less sophisticated and explicit. Second, as the interview data revealed, students’ inability occurred due to their limited knowledge of the issue and lack of knowledge in applying their critical thinking in writing particularly in the expository genre. The findings above suggest that the students need more guidance so that they have a better command of some critical thinking components to develop their critical thinking, especially their capacity to argue, to state opinions and stance explicitly and carefully. All these may also reflect the urgency to provide the students in the site with a great deal of assistance in a writing process and efforts to expose students to some teaching programs with a view to improving their critical thinking in the future. ABSTRACT